Infowhelm : environmental art and literature in an age of data - Houser, Heather (Literature Now., 2020)
"How do artists and writers engage with environmental knowledge in the face of overwhelming information about catastrophe? What kinds of knowledge do the arts produce when addressing climate change, extinction, and other environmental emergencies? What happens to scientific data when it becomes art? In Infowhelm, Heather Houser explores the ways contemporary art manages environmental knowledge in the age of climate crisis and informational overload. Houser argues that the infowhelm -- a state of abundant yet contested scientific information -- is an unexpectedly resonant resource for environmental artists seeking to go beyond communicating stories about crises. Infowhelm analyzes how artists transform the techniques of the sciences into aesthetic material, repurposing data on everything from butterfly migration to oil spills and experimenting with data collection, classification, and remote sensing. Houser traces how artists ranging from novelist Barbara Kingsolver to digital memorialist Maya Lin rework knowledge traditions native to the sciences, entangling data with embodiment, quantification with speculation, precision with ambiguity, and observation with feeling. Their works provide new ways of understanding environmental change while also questioning traditional distinctions between types of knowledge. Bridging the environmental humanities, digital media studies, and science and technology studies, this timely book reveals the importance of artistic medium and form to understanding environmental issues and challenges our assumptions about how people arrive at and respond to environmental knowledge"--